THE FORMATION OF THE PHILOSOPHICAL AND AESTHETIC VIEWS OF THEODORE DREISER, A PROMINENT REPRESENTATIVE OF NATURALISM - Saakyan Roza Yurevna (Western European Studies, 2024)
This article examines the key factors that played a major role in shaping the philosophical and aesthetic views of Theodore Dreiser, an American writer and journalist, and one of the leading representatives of naturalism in American literature. The article also analyzes the main mechanisms through which Dreiser not only critiques the social and economic structures that contribute to inequality but also mocks the naive belief in unlimited opportunities for individual growth within such a system. His irony is aimed at exposing the myths that uphold the status quo and calls for a deeper understanding of what it truly means to be successful and what values should be at the center of public attention.
Keywords: philosophy; naturalism; reality; illusion